HR practices and turnover intention: the mediating roles of organizational commitment and organizational engagement in a selected region in Malaysia - Juhdi, Nurita (Routledge Informa Ltd, 2013)
This study examined the mediating effects of organizational commitment (OC) and organizational engagement (OE) on the relationship between human resource (HR)practices (career management, performance appraisal, compensation, person–job fit and job control) and turnover intention. A total of 457 employees working in various sectors in a selected region in Malaysia participated in this study. It was found that all the variables used to measure HR practices have significant effects on OC and OE. However, multiple regression analyses indicated that career management and job control did not have any significant influence on turnover intention. OC and OE were discovered to give partial mediating effects on the relationship between HR practices and turnover intention.